2010
DOI: 10.1161/circep.109.858381
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Pulmonary Vein Antral Isolation in Patients With Obstructive Sleep Apnea

Abstract: Background— Obstructive sleep apnea (OSA) may be associated with pulmonary vein antrum isolation (PVAI) failure. The aim of the present study was to investigate if treatment with continuous positive airway pressure (CPAP) improved PVAI success rates. Methods and Results— From January 2004 to December 2007, 3000 consecutive patients underwent PVAI. Patients were screened for OSA and CPAP use. Six hundred forty (21.3%) patients had OSA. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
1
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 26 publications
4
137
1
18
Order By: Relevance
“…Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF. Redukcja czynników ryzyka oraz wentylacja z ciągłym dodatnim ciśnieniem w drogach oddechowych mogą ograniczać nawroty AF [308][309][310][311][312]. Wydaje się rozsąd-nym rozważanie przesiewowego wykrywania obturacyjnego bezdechu sennego u pacjentów z AF i obciążonych czynnikami ryzyka.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF. Redukcja czynników ryzyka oraz wentylacja z ciągłym dodatnim ciśnieniem w drogach oddechowych mogą ograniczać nawroty AF [308][309][310][311][312]. Wydaje się rozsąd-nym rozważanie przesiewowego wykrywania obturacyjnego bezdechu sennego u pacjentów z AF i obciążonych czynnikami ryzyka.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…268,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298 A recent meta-analysis identified 16 studies involving 5864 individuals reporting on the link between obesity and recurrence of AF after catheter ablation, identifying that there was a 3.1% greater risk of recurrent AF postablation for every one unit increase in BMI (RR 1.03; 95% CI 1.00–1.07). 299 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…283,289,290,291,316,317,318,319 Although OSA has been associated with poorer outcomes, CPAP appears to attenuate the deleterious impact of OSA. Pooled analysis suggests that although OSA increases the risk of AF recurrence following ablation (RR 1.31; 95% CI 1.16–1.48; P <.001), CPAP therapy improves ablation success to rates comparable with non-OSA populations (RR 1.25; 95% CI 0.77–2.03; P = .37).…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with atrial fibrillation, the prevalence of OSA has been found to be between 21% and 49% [64,65], and it is higher in patients with lone atrial fibrillation, compared to matched control subjects with other cardiovascular disease (49% versus 32%) [64,66].…”
Section: Observational Studies Regarding Atrial Fibrillationmentioning
confidence: 99%